Outcomes Related to Antiplatelet Therapy in a High-Risk ST-Segment Elevation Myocardial Infarction Population: A Retrospective Real-World Analysis of an Italian ECMO Center. (May 2020) - Righetti, Stefano; Montemerlo, Elisabetta; Soffici, Federica; Sala, Davide; Bozzano, Alessandro; Mauro, Andrea; Maggioni, Elena; Avalli, Leonello; Camisasca, Paola; Colombo, Virgilio; Achilli, Felice; Lettino, Maddalena; et al.
Aim: To evaluate outcomes related to antiplatelet therapy in patients with ST-elevation myocardial infarction (STEMI) admitted to the San Gerardo Hospital in Monza, an extracorporeal membrane oxygenation (ECMO) reference center in the Monza-Brianza area. Methods: This retrospective study enrolled patients with STEMI hospitalized between 2013 and 2017. Results: This study included 653 patients (mean age: 67.5 years, 71% male). Across the study period, ticagrelor use showed consistent increases, from 22% of patients during 2013 to 85% in 2017. Cardiac arrest prehospitalization occurred in 100 patients (15.3%), either at home (n = 85, 13.0%) or during transfer (n = 15, 2.3%); 46 patients underwent ECMO for refractory cardiac arrest. Rates of 90-day survival (hazard ratio [HR]: 2.4, 95% confidence interval [CI]: 1.3-4.4, P = .004) and ST resolution (odds ratio [OR]: 2.5, 95% CI: 1.6-4.1, P = .000) were higher with ticagrelor than with other antiplatelet agents. When analyzed by each agent, patients on ticagrelor had longer survival (HR: 0.4, 95% CI: 0.2-0.8, P = .008) than patients on clopidogrel and more frequent ST resolution than those on clopidogrel or prasugrel (OR: 0.4, 95% CI: 0.2-0.7, P = .002 and OR: 0.4, 95% CI: 0.2-0.7, P = .006). There was no difference in mortality between ticagrelor and prasugrel. Conclusions: Changes in the treatment of high-risk patients with STEMI over time are in line with changes in treatment guidelines. In these patients, ticagrelor is associated with significantly improved 90-day mortality compared with clopidogrel.